The predictive value of early treatment response in antipsychotic-naive patients with first-episode psychosis: Haloperidol versus olanzapine. (30th July 2016) - Rasmussen, Sean A.; Rosebush, Patricia I.; Anglin, Rebecca E.; Mazurek, Michael F.
Abstract: Early antipsychotic response predicts outcomes for psychotic patients, but recent evidence suggests that this may not be true for patients treated with olanzapine. In this study, we assessed the predictive value of early response to olanzapine or haloperidol in 75 antipsychotic-naive, first-episode psychosis inpatients. Patients were assessed weekly using the Brief Psychiatric Rating Scale (BPRS), Hamilton Depression Rating Scale (HAM-D), Hamilton Anxiety Rating Scale (HAM-A), and Young Mania Rating Scale (YMRS). Regression analyses were used to determine whether improvement at week 2 or week 3 predicted improvement at hospital discharge. The majority of patients in both groups experienced a decrease in symptom severity of ≥50% at week 2. In the haloperidol group, week 2 improvement predicted improvement at discharge for all measures except the HAM-A. In the olanzapine group, week 2 improvement only predicted improvement at discharge for HAM-D scores. However, week 3 improvement in the olanzapine group predicted improvement at discharge for all measures except the HAM-A. Olanzapine non-responders at week 3 (but not week 2) benefited from having olanzapine switched to another antipsychotic. These results suggest that a 2 week trial of haloperidol is sufficient to predict treatment outcomes, while a 3 week trial is required for olanzapine. Highlights: We examined the predictive value of early antipsychotic response at week 2 or week 3. Response to haloperidol at hospital discharge could be predicted by week 2. Response to olanzapine at hospital discharge could not be predicted until week 3. Olanzapine non-responders at week 3 benefited from switching to another antipsychotic. Patients in both treatment groups experienced a rapid and strong treatment response.